(untitled) (Third Sector Social Economic Review, 2026)
The aim of this study is to empirically examine the effect of working capital management on firm performance. Accordingly, the quarterly financial data of 33 firms operating in the BIST Energy sector for the period 2020Q4–2025Q3 were analyzed using panel data analysis. The financial performance of the firms was represented by ROA and ROE. The impact of working capital management was evaluated both through general strategies such as working capital investment and financing policies, and through working capital management components such as cash conversion cycle, payables period, receivables period, and inventory turnover period. The analysis results revealed that the working capital investment policy has a significant effect on both return on assets and return on equity. The coefficients related to the components of working capital management were found to be statistically insignificant. Additionally, it was observed that increases in the current ratio and firm size, included as control variables in the study, enhance firm performance.